Developing Performance Assessment-Based Authentic Assessment of Business Plan Subject - Vica Vekyana Sagita; Wening Patmi Rahayu (Faculty of Economics, State University of Jakarta., 2019)
The purpose of this research and development was to produce a product in the form of an authentic assessment instrument on cognitive and psychomotor aspects based on performance assessment in productive learning of business plan subject that was valid and feasible to be implemented in Vocational High School or SMK. The model of the research adopted Borg & Gall's Research and Development (R&D) model. The model used six-stages model of ten stages which were performed, namely: (1) potential and problems; (2) data collection; (3) development of product drafts; (4) limited trials; (5) revision of the trial results; and (6) final products. In producing a research product, it was necessary to perform the content validation and limited trial tests. The validation test was carried out by 3 lecturers and 1 Business Plan teacher who met the criteria as a validator. Exercises in Students’ Worksheets (LKS) were analyzed with the level of difficulty and the discrimination power level. The results of the study were the instrument products in the form of Student Worksheets (LKS) on cognitive and psychomotor assessment based on performance assessment for the business plan subjects were considered valid and feasible, in form of test and non-test questions, performance assessment sheets which were used to assess student performance when practicing business plan learning materials. Meanwhile, the quality of the questions used have also met the level of difficulty and the discrimination power level.